Enhanced influenza A H1N1 T cell epitope recognition and cross-reactivity to protein-O-mannosyltransferase 1 in Pandemrix-associated narcolepsy type 1 - Vuorela A; Freitag TL; Leskinen K; Pessa H; Härkönen T; Stracenski I; Kirjavainen T; Olsen P; Saarenpää-Heikkilä O; Ilonen Jorma; Knip M; Vaheri A; et al. (NATURE RESEARCH, 2022)
Narcolepsy type 1 (NT1) is a chronic neurological disorder having a strong association with HLA-DQB1*0602, thereby suggesting an immunological origin. Increased risk of NT1 has been reported among children or adolescents vaccinated with AS03 adjuvant-supplemented pandemic H1N1 influenza A vaccine, Pandemrix. Here we show that pediatric Pandemrix-associated NT1 patients have enhanced T-cell immunity against the viral epitopes, neuraminidase 175-189 (NA175-189) and nucleoprotein 214-228 (NP214-228), but also respond to a NA175-189-mimic, brain self-epitope, protein-O-mannosyltransferase 1 (POMT1675-689). A pathogenic role of influenza virus-specific T-cells and T-cell cross-reactivity in NT1 are supported by the up-regulation of IFN-γ, perforin 1 and granzyme B, and by the converging selection of T-cell receptor TRAV10/TRAJ17 and TRAV10/TRAJ24 clonotypes, in response to stimulation either with peptide NA175-189 or POMT1675-689. Moreover, anti-POMT1 serum autoantibodies are increased in Pandemrix-vaccinated children or adolescents. These results thus identify POMT1 as a potential autoantigen recognized by T- and B-cells in NT1.